THE EFFECTIVENES OF ROLE PLAY IN IMPROVINGENGLISH SPEAKING SKILLTO THE TENTH GRADE STUDENTS OF MA NIDA’UL KHAIRAAT POMBEWE - seli seli; Yuni Amelia (Datokarama English Education Journal, 2021)
This study aims to determine the process of improving speaking skill through role play for tenth grade students of MANida'ul Khairaat Pombewe in the academic year 2020/2021. This study used pre-experimental design research methods. The researcher chose class 10thas a sample consisting of 10 students. In collecting the data, researchers used four types of instruments, namely: pre-test, treatment, post-test and documentation. The result of the data calculation showed that mean score of the students’ pre-test was 40.9, it was lower than the mean score of post-test 52.6. In analyzing the data the researchers used the 0.05 and 0.01 degree of significance and df (degree of freedom) N-1. This study has two hypothesis which are the null hypothesis or Ho (there is no improvement of using role play to the students’ speaking skill, and the alternative hypothesis or Ha (there is improvement of using role play to the students’ speaking skill). It can be concluded that Ho was rejected and Ha was accepted. The use of role play was effective to improve the students speaking skill at the tenth grade of students in MA Nida’ul Khairaat Pombewe.